The concepts of nationality and citizenship in the XXI century’s immigration scenario: an agonistic approach - Gueraldi, Michelle (Frontiers in Human Dynamics, 2025)
The legal concept of citizenship as it is built on liberal democratic orders, a universalized form of government, establishes nationality as the primary political link between the state and the citizen. We argue that this political composition creates a framework of antagonism between the national, as a citizen, and the foreigner, as a non-citizen, someone who does not belong to the national political community and thus threatens the cohesion between its members and between the people and the government of a nation-state. We counter-argue, however, that the new immigration triggered from the end of the colonial era to the present, has established itself as an organic phenomenon, an analytical category used by Antonio Gramsci linked to Mouffe and Laclau’s theoretical perspective, in particular regarding the paradigm of radical pluralist democracy. We highlight in particular the consolidation of collective subjects such as diasporas, whose members maintain an ambiguous relationship of identification with the nationality of their home state and the state where they are, physically. Mouffe and Laclau’s agonistic perspective allow us to understand the configuration of power relations that structure the social order and the type of hegemony they construct in their intersections with the work of Hannah Arendt, in the field of political philosophy, as well as historians, such as Eric Hobsbawm and Thomas Marshall, besides Carl Rogers. We intend to deconstruct to reconstruct the concepts of citizenship and nationality as placed on the political arena, as resulting of hegemonic articulations that lead to the maintenance of harmonious and non-violent social orders, as the opposite of the political dominance. The exclusion of the person, which always emerges, generates struggle, resistance, but not through an undifferentiated inclusion, but through inclusion as a particular person, who exercises the power to be what he is, in freedom, what is the root of citizenship, an instrument for emancipation.